Unconscious collusion: An interpretative phenomenological analysis of the maternity care experiences of women with obesity (BMI≥30 kg/m²). (June 2017) - Atkinson, Sandra; McNamara, Patricia Mannix
Abstract: Background: obstetric and midwifery literature continually emphasise incidence and consequence of obesity in pregnancy. However, they offer less consensus on how best to support women who are obese. Therefore, this study explores in depth the lived experience of women who have a Body Mass Index (BMI) ≥30 kg/m². This exploration provides a bio-psycho-social understanding of the lived experience of women to identify how best to support them throughout their childbirth experience. Methods: an Interpretative Phenomenological Analysis (IPA) design was adopted for this qualitative study. Purposive sampling of participants was conducted on the postnatal wards of a maternity hospital in the Republic of Ireland. In total, 15 participants volunteered to take part in semi-structured interviews conducted at six to ten weeks postnatally. Data were analysed utilising the IPA framework. Findings: the results indicate that participants were conscious of the problematics of communicating obesity in pregnancy. The narrative data revealed an unconscious collusion between healthcare professionals and women as they navigate obesity related conversations. The behaviours related to unconscious collusion are incorporated in the sub-ordinate themes; 'just recorded and that's all', 'but what's eating healthy? 'pussy footing around' and 'I hate that word obesity. Conclusions and implications for practice: the findings highlight a lack of information received by participants from healthcare professionals regarding increased BMI or weight management. The data suggests that healthcare professionals appeared to collude with women to avoid challenging discussions regarding obesity. This may be related to avoidance on participants' part and/or may be linked with healthcare professionals' reluctance to communicate issues relating to increased BMI. Although participants were generally unhappy with the communication skills of health professionals, they readily acknowledged the sensitive nature of obesity related communications. The findings provide healthcare professionals with an important insight into issues of effective communication and obesity related healthcare promotion from the woman's perspective in order to enhance provision of appropriate health information and maternity care to women who have an increased BMI. Highlights: Women and healthcare professionals appear to collude to navigate or avoid obesity related conversations. Woman identified a lack of consistent and relevant information. Woman recognised the sensitive nature of communicating issues around obesity. Training and support is required to equip healthcare professionals to engage in obesity related conversations.